Reusable boxes for a beneficial apple cold chain: A precooling analysis. (October 2019) - Gruyters, W.; Defraeye, T.; Verboven, P.; Berry, T.; Ambaw, A.; Opara, U.L.; Nicolai, Bart
Highlights: Apple precooling in plastic crates compared to cardboard standard. CFD simulations align well with experimental cooling characteristics. Use of internal packaging materials severely affects cooling performance. Uniformity of precooling better in plastic crates. Energy use is significantly less for precooling in plastic crates. Abstract: Single-use ventilated corrugated cardboard boxes are commonly used in the postharvest apple cold chain but pose significant challenges for optimising cooling efficiency while reducing energy use. The cooling performance of typical corrugated boxes (standard type 'Mk4') was compared to that of an alternative reusable plastic crate (RPC). Cooling rates, temperature uniformity, energy consumption and fruit quality were evaluated. Using a computational analysis, trade-offs between cooling rates and energy consumption were captured. Experiments were conducted in similar conditions to successfully verify computations and gain additional insights. A mismatch between the position of vent holes and fruit-supporting trays created isolated regions for the airflow, resulting in large temperature heterogeneities in the standard Mk4 box. Both cooling uniformity and energy use were found to be the best for RPCs, but the high airflow rates might cause chilling injury to the apples. Compared to corrugated boxes, RPCs showed promising features towards more energy-efficient cold chains.